Investigations into the effectiveness of fly ash and fruit seed based ash for the removal of boron from seawater - Ahmed, Roxanne Nahar (Curtin University, 2011)
Boron, if present in drinking water above the recommended level can cause health problems and adversely affect the environment. As such, the boron concentration in both drinking water and wastewater discarded to the environment is limited by various guidelines and regulations. Many desalination plants, especially those utilising seawater as feed water, have trouble in reducing boron levels to the drinking water standards. The current methods used to achieve the recommended limits, such as second pass RO systems and ion exchange resins, are generally expensive or energy intensive. It has been estimated that additional costs for boron removal to a level of 0.4 mg/l were in a range of 0.05-0.07 USD/m3 in a large system and 50% more in small Reverse Osmosis system. Incorporating an effective, economical method to remove boron would allow for significantly lower power consumption and operating costs. The scope of this study is to investigate the removal of boron from seawater using three easy, low cost methods. These methods are adsorption by natural fruit seed ash, adsorption by power plant fly ash, and coagulation with ferric chloride.Jar tests were carried out with ferric chloride, ash from power plants and fruit seed based material. Measured amounts of the chosen test material were added to jars containing a set volume of seawater and adjusted for pH. After the required contact time, samples were filtered and tested for boron concentration. The tested parameters included pH, reaction time and liquid/solid (L/s) ratio. Results suggested that our selected fruit based ash had remarkably higher removal efficiencies of boron (73%) compared to the fly ash and coagulants that were tested. Optimum removal efficiency was observed with the fruit seed ash at pH of 7 and L/s of 2. The results from the present work are of particular significance as the fruit seed ash showed highest removal efficiency at a neutral pH. This is especially important in reverse osmosis (RO) processes as it would enable better membrane stability and minimal membrane scaling, thus allowing for less maintenance and lower operating costs.